Listening to the experts: Parents' perspectives around infection risk and returning to education and social activities following their child's diagnosis of acute lymphoblastic leukemia. Issue 6 (14th May 2021) - Ballantine, Kirsten; Gooder, Claire; Ryan, Elizabeth; Macfarlane, Scott
Abstract: Background: During a child's prolonged treatment for acute lymphoblastic leukemia (ALL), there is a need to balance their increased risk of developing infection‐related complications with meeting their educational and social needs. Aims: To determine the safe timing of return to social activities for children undergoing treatment for ALL and to determine how parents perceive and act on advice related to infection risk while navigating their child's "return to normal." Methods and results: Medical and educational attendance records were reviewed for 47 children who were diagnosed with ALL and 24 semi‐structured qualitative interviews were conducted with a representative sample of their parents. The majority of children (69%) did not return to education prior to the start of maintenance therapy regardless of the advice that the families received from their healthcare team. Those who returned earlier were at no greater risk of major infection complications (mean = 0.5) than those who did not return until after commencing maintenance (mean = 0.4, P = .74). Parents spoke of the difficulty in obtaining practical, consistent, and timely advice and of balancing infection risk with a desire to return to normalcy. Inconsistent advice and constant vigilance placed a burden on parents which often profoundly affected their mental wellbeing. Overall, parents wanted to make their own decisions about how and when their child returned to education and social activities. They made these decisions based on many factors, of which infection risk was just one. Conclusion: Following the study conclusion, a national working group was established—including parent representatives—to implement the study recommendations. This includes the development of a range of practical resources to better support families. Health professional guidelines provide quantitative data pertaining to infection risk, while emphasizing that the returning decisions ultimately rest with the families. This research demonstrates that listening to parents—who are the experts through their lived experiences—is a critical element in creating policies that are responsive, meaningful, and widely accepted.